Use of Wearable Devices to Analyze the Student Engagement in Physical Education - Munawar, Iqra; Akhter, Shagufta; Farah, Hummaira (ACADEMIA International Journal for Social Sciences, 2026)
This study aims to analyze the influence of step tracking and heart rate monitoring on student engagement in physical education classes using AI tools. The study sought to ascertain if acceptance scores from the Technology Acceptance Model (TAM) predicted physical activity. A sample of 86 college students, ages 16 to 22. Wearable device indications such as step count, distance traveled, average heart rate, minutes of moderate-to-vigorous physical activity (MVPA), and engagement levels were used to gather data. IBM SPSS Statistics Version 27 was used to perform statistical analysis. Multiple regression analysis, ANCOVA, Pearson correlation analysis, paired sample t-tests, independent sample t-tests, and descriptive statistics were used. At p <.05, statistical significance was determined. Students who wore wearable timepieces outperformed the control group in terms of step counts (8,945 ± 1,120), distance traveled (5.8 ± 1.1 km), average heart rate (136.4 ± 10.3 bpm), MVPA minutes (28.6 ± 5.2), and engagement scores (4.18 ± 0.52).